THE INFLUENCE OF PRODUCT QUALITY, SERVICE QUALITY, AND ELECTRONIC WORD OF MOUTH ON PURCHASE INTENTION - Felix Enrico Evan Harianto; Zeplin Jiwa Husada Tarigan (Petra Christian University, 2026)
This study aims to analyze the influence of product quality, service quality, and electronic word of mouth on purchase intention among Serabi Notosuman Surakarta consumers. The study used a quantitative approach with a purposive sampling technique. Data were obtained through online questionnaires distributed to consumers who had visited or purchased at least twice and were at least 17 years old. Of the 102 questionnaires collected, 98 met the criteria and were used in the analysis. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 3.0. The results showed that product quality had no significant effect on purchase intention (β = 0.237; p = 0.161) or electronic word of mouth (β = 0.165; p = 0.148). Conversely, service quality had a positive and significant effect on purchase intention (β = 0.397; p = 0.001) and electronic word of mouth (β = 0.536; p < 0.001). Electronic word of mouth also had a positive and significant effect on purchase intention (β = 0.266; p = 0.008). These findings indicate that consumer purchase intention is more influenced by service quality and online consumer reviews or recommendations than by direct product quality. Therefore, management needs to maintain product quality while prioritizing improving service quality and managing electronic word of mouth to strengthen consumer purchase intention.